The effects of supply management and supply network & supplier flexibility on supplier performance in supermarkets in Klang Valley / Siti Anis Adilah Tarmizi - Tarmazi, Siti Anis Adilah (2013)
Supply chain is required to be able to produce various different products and deliver to market in an acceptable speed and cost in order to be competitive in the marketplace. As the basis of competition expands to the supply chain and time also becomes increasingly important, flexibility of the supply chain has become a critical issue (Duclos, Vokurka, and Lummus, 2003). Thus, the purposes of this study are to determine the mediating effect of supply network and supplier flexibility on the relationship between supply management and supplier performance. This research is based on a quantitative approach using a self-administered questionnaire which was conducted at 79 participating supermarkets. Additionally, a causal research is undertaken to identify the relationship between supply management and supplier performance and the effect of supply network and supplier flexibility on this relationship. This study focused on the supermarkets in Klang Valleys’ supply chain setting and the data gathered were then analyzed using statistical tests such as reliability test and multiple regression analysis. The assumption that supply network and supplier flexibility mediates the relationship between supply management and supplier performance was proven by mediating analysis using Baron and Kenny approach. The findings also revealed that supply management predicts supplier performance. On the other hand, supply management which consists of supplier selection (p = .136), supplier development (p = .222) and strategic supplier alliances (p = .816) did not predict supply network and supplier flexibility. Therefore, this study perhaps can assist the management of supermarkets in Malaysia to gain awareness about the importance of practicing good supply management to ensure that they can help their suppliers to have more integrity and flexibility in supplying food products which later on can increase the performance of these suppliers.